2024
DOI: 10.1002/ece2.29
|View full text |Cite
|
Sign up to set email alerts
|

Dual doping: An emerging strategy to construct efficient metal catalysts for water electrolysis

Zhijie Chen,
Ning Han,
Wei Wei
et al.

Abstract: Developing efficient electrocatalysts for water electrolysis is critical for sustainable hydrogen energy development. For enhancing the catalytic performance of metal catalysts, dual doping has attracted enormous interest for its high effectiveness and facile realization. Dual doping is effective for tuning the electronic properties, enhancing the electrical conductivity, populating active sites, and improving the stability of metal catalysts. In this review, recent developments in cation–cation, cation–anion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 217 publications
0
2
0
Order By: Relevance
“…Unfortunately, a trade-off dilemma between increased efficiency and decreased cost remains the major bottleneck for large-scale hydrogen production. Indeed, state-of-the-art electrocatalysts for water electrolysis with high efficiency generally consist of expensive and scarce noble metals, such as Pt, RuO2, and IrO 2 . In sharp contrast, the activities of low-cost and earth-abundant transition metal-based catalysts, including metals, oxides, phosphides, chalcogenides, nitrides, and carbides, still fell short compared to precious metal catalysts. Therefore, a rational design of cost-effective, efficient bifunctional electrocatalysts for water electrolysis at the industrial level is required.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a trade-off dilemma between increased efficiency and decreased cost remains the major bottleneck for large-scale hydrogen production. Indeed, state-of-the-art electrocatalysts for water electrolysis with high efficiency generally consist of expensive and scarce noble metals, such as Pt, RuO2, and IrO 2 . In sharp contrast, the activities of low-cost and earth-abundant transition metal-based catalysts, including metals, oxides, phosphides, chalcogenides, nitrides, and carbides, still fell short compared to precious metal catalysts. Therefore, a rational design of cost-effective, efficient bifunctional electrocatalysts for water electrolysis at the industrial level is required.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a further enhancement in the reaction activity for synthesizing DMC from methanol and CO 2 . 23 For example, Liu et al 24 reported on Zr-doped CeO 2 nanorods for DMC synthesis from methanol and CO 2 . They observed that Zr insertion into the lattice of CeO 2 formed a solid solution, facilitating the creation of more oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%